America adopts the automobile 1895 - 1910 - Flink, James J. (MIT Press, 1970)
In this revision, as in the original text, a strong emphasis has been placed on the role played by intuition, beause of its power to suggest the basic concepts of mathematics, to give th driving force for investigation, and to furnish the indealizations used in applications.